Possibilities of Efficient Recycling of Textile-Sewing Fiber Waste and Application in the Flower Printing Process - Abdumajidov Anvar Abdumalikovich; Nabieva Iroda Abdusamatovna; Mirataev Abdumalik Abdumadjidovich; Irmatova Muharram Botyrovna (Researchparks Publishing, 2022)
The article presents the results of the research on the possibility of using fiber waste of the textile-garment industry in order to increase the efficiency of their processing and application in the processes of printing flowers on fabric. The possibility of decolorization and bleaching of fiber wastes dyed with different classes of dyes and their use as a thickener in dyeing with active and cube dyes is shown. As a result of research, it has been shown that the sodium alginate thickener imported to our Republic, which is used in flower printing, can be fully and partially replaced by the color depth of the patterns formed on the surface of the fabric, the clarity of the border line, color intensity and resistance to various effects.